2022
DOI: 10.1039/d2ma00633b
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid organic–inorganic perovskites as microwave radiation switches

Abstract: Hybrid organic-inorganic perovskites form an intensively growing class of functional materials which attract huge attention due to their various practically important functionalities. In this paper we show the ability of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…[1][2][3] Addition of conductive ingredients as well as electrical-and magnetic-field-oriented admixtures into composite materials, and the application of molecular materials with phase transition are commonly accepted and intensively studied techniques. [4][5][6][7] In the latest research, [8][9] were shown the newest possibilities of CoFe 2 O 4 and Fe 3 O 4 for electromagnetic wave DOI: 10.1002/apxr.202300090 absorption in the form of lightweight foam controlled by 3D structure. This proved the high efficiency of the use of ultra-thin films and their combinations for such applications.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Addition of conductive ingredients as well as electrical-and magnetic-field-oriented admixtures into composite materials, and the application of molecular materials with phase transition are commonly accepted and intensively studied techniques. [4][5][6][7] In the latest research, [8][9] were shown the newest possibilities of CoFe 2 O 4 and Fe 3 O 4 for electromagnetic wave DOI: 10.1002/apxr.202300090 absorption in the form of lightweight foam controlled by 3D structure. This proved the high efficiency of the use of ultra-thin films and their combinations for such applications.…”
Section: Introductionmentioning
confidence: 99%